Spatial Variability in Patterns of Glacier Change across the Manaslu Range, Central Himalaya - Robson, Benjamin A.; Nuth, Christopher; Nielsen, Pål R.; Girod, Luc; Hendrickx, Marijn; Dahl, Svein Olaf (Frontiers in Earth Science, 2018)
This study assesses changes in glacier area, velocity and geodetic mass balance for the glaciers in the Manaslu region of Nepal, a previously undocumented region of the Himalayas. We studied changes between 1970 (for select glaciers), 2000, 2005 and 2013 using freely available Landsat satellite imagery, the SRTM Digital Elevation Model (DEM) and a DEM based on Worldview imagery. Our results show a complex pattern of mass changes across the region, with glaciers lowering on average by -0.25 ± 0.08 m a-1 between 2000 and 2013 which equates to a negative geodetic mass balance of -0.21 ± 0.16 m w.e.a-1. Over approximately the same time period (1999 to 2013) the glaciers underwent a -16.0% decrease in mean surface velocity over their debris-covered tongues as well as a reduction in glacier area of -8.2%. The rates of glacier change appear to vary between the different time periods, with glacier losses increasing in most cases. The glaciers on Manaslu itself underwent a change in surface elevation of -0.46 ± 0.03 m a-1 between 1970 and 2000 and -0.99 ± 0.08 m a-1 between 2000 and 2013. Rates of glacier area shrinkage for the same glaciers increased from -0.36 km2 a-1 between 1970 and 2001 to -2.28 km2 a-1 between 2005 and 2013. Glacier change varies across the region and seems to relate to a combination of glacier hypsometry, glacier elevation range and the presence and distribution of supraglacial debris. Lower-elevation, debris-free glaciers with bottom-heavy hypsometries are losing most mass. As the glaciers in the Manaslu region continue to stagnate, an accumulation and thickening of the debris-cover is likely, thereby insulating the glacier and further complicating future glacier responses to climate.